2023
DOI: 10.1111/jdv.18926
|View full text |Cite
|
Sign up to set email alerts
|

The burden of alopecia areata: A scoping review focusing on quality of life, mental health and work productivity

Abstract: Alopecia areata (AA) is a common inflammatory autoimmune disease of the hair which can have a significant negative impact on quality of life (QoL), mental health and productivity. The aim of this scoping review is to elucidate the burden of AA focusing on these three realms. Inclusion criteria included all original manuscripts with no restriction on study type or statistical method written in English (or having an English abstract). For QoL 40 articles were included, 85 for psychiatric comorbidities, and 9 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 135 publications
0
27
0
Order By: Relevance
“…One recent study demonstrated that employers feel less comfortable hiring individuals with AA [3]. These employer attitudes in combination with workplace bullying may contribute to the higher rates of work absenteeism, work productivity loss, and unemployment in patients with AA [6,7]. The culmination of psychosocial obstacles in the workplace and potentially lost income can compound the financial burden and distress experienced by this patient population [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrated that employers feel less comfortable hiring individuals with AA [3]. These employer attitudes in combination with workplace bullying may contribute to the higher rates of work absenteeism, work productivity loss, and unemployment in patients with AA [6,7]. The culmination of psychosocial obstacles in the workplace and potentially lost income can compound the financial burden and distress experienced by this patient population [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…This issue of JEADV focuses on the burden of this immune-mediated disease that is manifested by hair loss, as well as its strong association with depression. [8][9][10] It was found that up to 62% of patients make significant life decisions including relationships, education and career based on their alopecia areata. 8 Moreover, children and adolescents with hair loss often experience bullying, including physical aggression.…”
Section: Hair Loss Is a Symptom Of Many Complex Medical And Psycholog...mentioning
confidence: 99%
“…[8][9][10] It was found that up to 62% of patients make significant life decisions including relationships, education and career based on their alopecia areata. 8 Moreover, children and adolescents with hair loss often experience bullying, including physical aggression. 10 For us, physicians and for our patients, a disease associated with hair loss goes far beyond 'only hair (shafts)'.…”
Section: Hair Loss Is a Symptom Of Many Complex Medical And Psycholog...mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Alopecia areata may significantly affect a patient's appearance and impact on their health-related quality of life (HRQoL). 4,5 Reduced…”
mentioning
confidence: 99%